Sexing the sternal rib end in modern Greeks: A virtual osteometric approach using high-resolution 3D surface models - Ioanna Karagiorgou; Ioanna Anastopoulou; Fotios Alexandros Karakostis; Elena Kranioti; Konstantinos Moraitis (Homo)
Sex determination is one of the first biological attribute to be assessed when unidentified remains surface. In material of forensic interest, being able to use every skeletal element available for identification purposes is of paramount importance. The osteometric method from the sternal rib end has been found to generate accurate sex estimates, but as various studies have proved, all osteometric methods should be population-specific, as one equation does not fit all. The aim of this study is to assess sexual dimorphism in a contemporary Greek population sample of 68 males and 43 females, with the use of discriminant function analysis. The superior-inferior height (SIH) and anterior-posterior breadth (APB) from the third to fifth sternal rib ends of both sides were taken from 3D models created with the use of a hand-held 3D scanner. The results demonstrated that SIH is more sexually dimorphic than APB (alpha value of .05) while the application of İşcan’s (1985) formula on the contemporary Greek sample, provided results of low accuracy, ranging from 48.6–52.4%. The cross-validated discriminant functions equations for the current sample, produced results ranging between 74.0–82.9% indicating that population-specific formulas produce results of higher accuracy, that are vital in cases of forensic interest.